(untitled) (Journal of Philosophy Culture and Political Science, 2019)
Opening speech about a research subject. Article is devoted to the analysis of the educational migration directed from Kazakhstan to China. According to the author, educational immigration has both positive, and negative aspects. This process has several key effects for many countries and for development of Kazakhstan: political, economic, social and demographic. The purpose, the main directions and the ideas of scientific research – to study features of the international educational migration on the example of a student’s stream from Kazakhstan to China. Main directions of a research: to study historical, social and economic, cultural and psychological and other prerequisites of emergence of a student’s stream in the People’s Republic of China, to reveal features of functioning of a system of the international student’s mobility and to define the place of a stream from Kazakhstan to China in this system; to study existing in Kazakhstan intermediary the organizations, supporting receipt in the Chinese higher education institutions; to study the institutes promoting maintenance of a student’s stream and RK in the accepting cities of the People’s Republic of China, to describe process of formation of social networks of the Kazakhstan students in China. Short description of the scientific and practical importance of work. Educational migration is one of the most acute and problematic issues in modern society. Educational migration from RK in the People’s Republic of China in this case – not an exception. Therefore the author made an attempt to clear some main lines of this process. The scientific and practical value of this research does not raise doubts. The methodology of a research is based on system, comparative, content – and an event analysis. Educational migrations are a multidimensional phenomenon therefore also approaches to studying of migration of this type are many-sided. Main results and analysis, research conclusions: Educational migrations on number concede only to the labor and forced migrations and are considered as some of the most large-scale in the world. They occur both on international, and on interstate levels. Thus, obvious economic, social, political advantages of educational migration have to become the basis to make development of educational migration by an important part of migration policy of Kazakhstan. The value of the conducted research (the made contribution of this work to the corresponding field of knowledge) makes a contribution to development of a research of migration processes. Especially the research of obrazovtayelny migration and its features in terms of political science is of a particular research interest. The practical value of results of work allows to find the answer to a research question of the determinants setting the direction of educational migration and the international student’s mobility. Key words: the international educational migration, the higher education, academic mobility, the Kazakhstan-Chinese relations.